(untitled) (Journal of Engineering, 2009)
This paper reports eight tests in which in-plane shear forces are applied across the joint between two different concretes forming a composite action. Shear can be transmitted across the joint either by interlocking of the aggregate particles protruding from each face or by shearing of the reinforcement crossing the joint. Tests are conducted on initially cracked specimens by depending only on dowel action. The results of the tests are compared with theoretical results of the exponential equation presented by Millard and Johnson. The computer program of Al-Shaarbaf using the nonlinear behavior of concrete is used to perform the analysis with inclusion of the exponential equation for dowel action in the interface layer. The program uses 20-node brick elements with embedded bar elements. This program is also applied to Hofbeck et al. tests. The comparison shows that the experimental and the analytical results give good agreement where the difference between the two is between (2.5-5)% . The use of the exponential equation gives good results when the concrete is assumed to be initially cracked as in construction joints.